MANAJEMEN SARANA PRASARANA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN SERANG 3 - Kartika Santi Pratiwi; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
The background for this research was to see the condition of the school which was quite large for the elementary school level. The purpose of this research is to describe how the management of facilities and infrastructure in SDN Serang 3. The method used in this study is a qualitative method and data collection techniques by observation and interviews with related parties. The conclusion of this study is that based on the results of research related to the management of facilities and infrastructure in improving the quality of education at SDN Serang 3 it is good, all stages of management of facilities and infrastructure at SDN Serang 3 have been carried out starting from the planning, procurement, inventory, distribution, maintenance up to elimination and accountability. SDN Serang 3 at the planning stage, the team and the school principal have analyzed the school's needs such as what facilities and infrastructure are lacking and what facilities and infrastructure are needed. Schools use BOS funds effectively and efficiently. All facilities and infrastructure owned were purchased with BOS funds or assistance from the government. In the process of procuring facilities and infrastructure that was carried out at SDN Serang 3, a priority scale selection was carried out which prioritized facilities and infrastructure that really had to be expedited. Schools also carry out inventory properly and write off assets in accordance with applicable regulations and are accountable to the agency.